PERAN ADAT DAN PENSAKRALAN MATA AIR TERHADAP KONSERVASI AIR DI LERENG CIREMAI - Noerdjito, Mas; Royani, Mohammad Fathi; Widodo, Hawal (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTTraditional Role and Spring Sacredness For Water Conservation in the slope of MountCiremai. Kuningan Regency proclaimed as conservation regency. Consequently the way oflife in this regency should follow non-pollutant producing or non-environmental damagingactivities. This regency is intended to perform organic agriculture and water tourism (falls,lakes, and springs) destination. For those purposes, Kuningan Regency should maximize thepotency of natural catching and reserving rainfall area to be used efficiently thereafter.Kuningan Regency is surrounded by five DAS derived from the slope of Mount Ciremai. Atleast there are three sacred springs in Kuningan Regency including Balong Dalem, BalongCibulan, and Sumur Tujuh. All of them are located in Jalaksana District. Balong Dalem andSumur Tujuh are the centre of traditional ritual called kawin cai or mapag cai. The ritual implyingawareness of the society human life depend on water supply sustainability. Comparativeanalysis between sacred and non-sacred springs indicated that the sacred springs are betterand more conserved condition than that in non-sacred spring (Balong Darmaloka). However,there were still unique and threatened animals in sacred springs. Therefore, traditional rolesand spring sacredness in Kuningan are still needed for spring conservation. Unfortunately,many of governmental activities exhibited unawareness of local government to the springconservation which it should become their responsibility.Key words: Traditional ritual, water conservation, Ciremai, Kuningan Regency